Pengaruh Permainan Kubus untuk Perkembangan Motorik Halus Anak Usia 3-4 Tahun Di KB Aisyiyah 14 Sidokumpul - Fida Atiyah; Mushab Al Umairi; Fitri Ayu Fatmawati (Journal of Islamic Education for Early Childhood, 2024)
ABSTRACT This research was conducted because there is still a lack of fine motor development abilities in terms of hand skills in Play Group children. In this study, researchers saw children who still had difficulty folding paper, still felt amused by a texture that tended to be liquid and thick, played with finger painting, how to tear paper that was still being pulled and stick it using glue with a thick material. Seeing this, the researchers created a special game, namely the cube game. The cube game is a game created to help stimulate the development of children's fine motor skills, this game is made to be interesting for children. The aim of this research was to determine the influence of cube games on the fine motor development of children aged 3-4 years at KB Aisyiyah 14 Sidokumpul. This research uses a quantitative method with a One-Group Pre-Post Test Design. By taking samples using Nonprobability Sampling with Purposive Sampling technique, the sample used was 21 children. The data that has been obtained in the research shows that the average value of the Pretest and Posttest is 44, increasing to 80. The output value of the test statistics shows that it can be seen that the value of Asymp Sig (2-tailed) < 0.05, namely 0.000 < 0.05, then the hypothesis is accepted which shows the influence of the cube game to improve fine motor development at KB Aisyiyah 14 Sidokumpul. Keywords: Cube Game, Fine Motoric, Play Group